Question
upstudy study bank question image url

Write each expression in Exercises \( 1-14 \) in the form \( 2^{k x} \) or \( 3^{k x} \), for a suitable constant \( k \). \( \begin{array}{ll}\text { 1. } 4^{x},(\sqrt{3})^{x},\left(\frac{1}{9}\right)^{x} & \text { 2. } 27^{x},(\sqrt[3]{2})^{x},\left(\frac{1}{8}\right)^{x} \\ \begin{array}{ll}\text { (3) } 8^{2 x / 3}, 9^{3 x / 2}, 16^{-3 x / 4} & \text { 4. } 9^{-x / 2}, 8^{4 x / 3}, 27^{-2 x / 3} \\ \text { 5. }\left(\frac{1}{4}\right)^{2 x},\left(\frac{1}{8}\right)^{-3 x},\left(\frac{1}{81}\right)^{x / 2} & \text { 6. }\left(\frac{1}{9}\right)^{2 x},\left(\frac{1}{27}\right)^{x / 3},\left(\frac{1}{16}\right)^{-x / 2}\end{array}\end{array} \)

Ask by Clarke Brooks. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

Each expression is rewritten as \( 2^{k x} \) or \( 3^{k x} \) with the appropriate constant \( k \).

Solution

Sure! Let's rewrite each expression in the form \( 2^{k x} \) or \( 3^{k x} \), where \( k \) is a suitable constant. ### **1.** a) \( 4^{x} \) Since \( 4 = 2^2 \): \[ 4^{x} = (2^2)^{x} = 2^{2x} \] b) \( (\sqrt{3})^{x} \) Since \( \sqrt{3} = 3^{1/2} \): \[ (\sqrt{3})^{x} = (3^{1/2})^{x} = 3^{\frac{x}{2}} \] c) \( \left(\frac{1}{9}\right)^{x} \) Since \( \frac{1}{9} = 3^{-2} \): \[ \left(\frac{1}{9}\right)^{x} = 3^{-2x} \] --- ### **2.** a) \( 27^{x} \) Since \( 27 = 3^3 \): \[ 27^{x} = (3^3)^{x} = 3^{3x} \] b) \( \left(\sqrt[3]{2}\right)^{x} \) Since \( \sqrt[3]{2} = 2^{1/3} \): \[ \left(\sqrt[3]{2}\right)^{x} = 2^{\frac{x}{3}} \] c) \( \left(\frac{1}{8}\right)^{x} \) Since \( \frac{1}{8} = 2^{-3} \): \[ \left(\frac{1}{8}\right)^{x} = 2^{-3x} \] --- ### **3.** a) \( 8^{\frac{2x}{3}} \) Since \( 8 = 2^3 \): \[ 8^{\frac{2x}{3}} = (2^3)^{\frac{2x}{3}} = 2^{2x} \] b) \( 9^{\frac{3x}{2}} \) Since \( 9 = 3^2 \): \[ 9^{\frac{3x}{2}} = (3^2)^{\frac{3x}{2}} = 3^{3x} \] c) \( 16^{-\frac{3x}{4}} \) Since \( 16 = 2^4 \): \[ 16^{-\frac{3x}{4}} = (2^4)^{-\frac{3x}{4}} = 2^{-3x} \] --- ### **4.** a) \( 9^{-\frac{x}{2}} \) Since \( 9 = 3^2 \): \[ 9^{-\frac{x}{2}} = (3^2)^{-\frac{x}{2}} = 3^{-x} \] b) \( 8^{\frac{4x}{3}} \) Since \( 8 = 2^3 \): \[ 8^{\frac{4x}{3}} = (2^3)^{\frac{4x}{3}} = 2^{4x} \] c) \( 27^{-\frac{2x}{3}} \) Since \( 27 = 3^3 \): \[ 27^{-\frac{2x}{3}} = (3^3)^{-\frac{2x}{3}} = 3^{-2x} \] --- ### **5.** a) \( \left(\frac{1}{4}\right)^{2x} \) Since \( \frac{1}{4} = 2^{-2} \): \[ \left(\frac{1}{4}\right)^{2x} = 2^{-4x} \] b) \( \left(\frac{1}{8}\right)^{-3x} \) Since \( \frac{1}{8} = 2^{-3} \): \[ \left(\frac{1}{8}\right)^{-3x} = 2^{9x} \] c) \( \left(\frac{1}{81}\right)^{\frac{x}{2}} \) Since \( \frac{1}{81} = 3^{-4} \): \[ \left(\frac{1}{81}\right)^{\frac{x}{2}} = 3^{-2x} \] --- ### **6.** a) \( \left(\frac{1}{9}\right)^{2x} \) Since \( \frac{1}{9} = 3^{-2} \): \[ \left(\frac{1}{9}\right)^{2x} = 3^{-4x} \] b) \( \left(\frac{1}{27}\right)^{\frac{x}{3}} \) Since \( \frac{1}{27} = 3^{-3} \): \[ \left(\frac{1}{27}\right)^{\frac{x}{3}} = 3^{-x} \] c) \( \left(\frac{1}{16}\right)^{-\frac{x}{2}} \) Since \( \frac{1}{16} = 2^{-4} \): \[ \left(\frac{1}{16}\right)^{-\frac{x}{2}} = 2^{2x} \] --- Each expression is now expressed as either \( 2^{k x} \) or \( 3^{k x} \), where \( k \) is a constant.

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Extra Insights

Let's transform the expressions to the forms \( 2^{k x} \) or \( 3^{k x} \): 1. \( 4^{x} = (2^2)^{x} = 2^{2x} \) \( (\sqrt{3})^{x} = (3^{1/2})^{x} = 3^{x/2} \) \( \left(\frac{1}{9}\right)^{x} = (9^{-1})^{x} = (3^2)^{-x} = 3^{-2x} \) 2. \( 27^{x} = (3^3)^{x} = 3^{3x} \) \( (\sqrt[3]{2})^{x} = (2^{1/3})^{x} = 2^{x/3} \) \( \left(\frac{1}{8}\right)^{x} = (8^{-1})^{x} = (2^3)^{-x} = 2^{-3x} \) 3. \( 8^{2x/3} = (2^3)^{2x/3} = 2^{2x} \) \( 9^{3x/2} = (3^2)^{3x/2} = 3^{3x} \) \( 16^{-3x/4} = (2^4)^{-3x/4} = 2^{-3x} \) 4. \( 9^{-x/2} = (3^2)^{-x/2} = 3^{-x} \) \( 8^{4x/3} = (2^3)^{4x/3} = 2^{4x} \) \( 27^{-2x/3} = (3^3)^{-2x/3} = 3^{-2x} \) 5. \( \left(\frac{1}{4}\right)^{2x} = (4^{-1})^{2x} = (2^2)^{-2x} = 2^{-4x} \) \( \left(\frac{1}{8}\right)^{-3x} = (8^{-1})^{-3x} = (2^3)^{3x} = 2^{9x} \) \( \left(\frac{1}{81}\right)^{x/2} = (81^{-1})^{x/2} = (3^4)^{-x/2} = 3^{-2x} \) 6. \( \left(\frac{1}{9}\right)^{2x} = (9^{-1})^{2x} = (3^2)^{-2x} = 3^{-4x} \) \( \left(\frac{1}{27}\right)^{x/3} = (27^{-1})^{x/3} = (3^3)^{-x/3} = 3^{-x} \) \( \left(\frac{1}{16}\right)^{-x/2} = (16^{-1})^{-x/2} = (2^4)^{x/2} = 2^{2x} \)

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy